A Look in the Mirror: Reflected Efficacy Beliefs in Groups. (December 2013) - Litrico, Jean-Baptiste; Choi, Jin Nam
The present study integrates symbolic interactionism with Bandura's social cognitive theory by conceptualizing and examining socially reflected efficacy beliefs within groups. The data collected from 128 students in 39 project teams indicate that self-constructed and reflected images of self-efficacy are empirically distinct from each other; however, such is not the case for self-constructed and reflected images of team-efficacy. Consistent with our theoretical expectations, our multilevel polynomial regression analysis revealed that members engaged more in work collaboration and less in process hindrance when they perceived congruence between self-efficacy and reflected self-efficacy, between self-efficacy and team efficacy, and between reflected self-efficacy and team efficacy. Our results suggest that self-efficacy beliefs have a socially constructed nature, thus expanding social cognitive theory.